A study of the dosage and duration for levobupivacaine infusion by the caudal‐epidural route in infants aged 3‐6 months. Issue 2 (19th December 2018) - Vashisht, Rita; Bendon, Anju A.; Okonkwo, Ijeoma; Patel, Davandra; Fullwood, Catherine; Ogungbenro, Kayode; Aarons, Leon; Darwich, Adam S.
Summary: Background: The local anesthetic, levobupivacaine, is the safer enantiomer of racemic bupivacaine. Present protocols for levobupivacaine are based on studies and pharmacokinetic modeling with racemic bupivacaine. Aims: The aim is to investigate total serum levobupivacaine concentrations after a caudalepidural loading dose followed by a maintenance infusion over 48 hours in infants aged 3‐6 months. Methods: The clinical trial was conducted in eight infants aged 3‐6 months, undergoing bladder exstrophy repair. Pharmacokinetic modeling allowed optimization of clinical sampling to measure total levobupivacaine and α1 ‐acid glycoprotein and prediction of the effect of α1 ‐acid glycoprotein on levobupivacaine plasma protein binding. Results: The observed median total levobupivacaine serum concentration was 0.30 mg/L (range: 0.20‐0.70 mg/L) at 1 hour after the loading dose of 2 mg/kg. The median total levobupivacaine concentration after 47 hours of infusion, at 0.2 mg/kg/h, was 1.21 mg/L (0.07‐1.85 mg/L). Concentrations of α1 ‐acid glycoprotein were found to rise throughout the study period. Pharmacokinetic modeling suggested that unbound levobupivacaine quickly reached steady state at a concentration of approximately 0.03 mg/L. Conclusion: The study allows the development of a pharmacokinetic model, combining levobupivacaine and α1 ‐acid glycoprotein data. Modeling indicates that unbound levobupivacaine quickly reaches steady state once the infusion is started. Simulations suggest that it may be possible to continue the infusion beyond 48 hours.